Finite Element Modeling Failure Prediction of Hybrid Composite CFRP/GFRP - Ab Ghani, AF; Yaakob, Y; Jumaidin, R; Ali, MB; Shaharuzaman, MA; DharMalingam, S (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
This study deals with the effect of different layup and orientation of carbon fiber reinforced plastics (CFRP) and glass fiber reinforced plastics (GFRP) composite materials and predict on the deformation and failure of CFRP and GFRP composite materials using finite element modelling (FEM) method using ANSYS. In this study, the composite is modelled in eight different arrangement of cases in terms of different plies arrangement and different angle of orientation. This paper focuses on the simulation for tensile test and failure prediction. For all the cases of a different arrangement of the composite coupon is generated using the CFRP and GFRP which based on standard on the manufacturer data sheet. The mesh convergence analysis is carried out before starting the simulation. Next, the validated method is implemented to proceed with the composite specimen for the tensile test with displacement control and failure prediction which is last ply failure. The last ply failure is used to find the maximum load of the composite that can withstand with the apply loads by using maximum stress theory and maximum strain theory.